Simulations of the Frequency Modulated Atomic Force Microscope (FM-AFM) nonlinear control system - Bueno, Atila Madureira [UNESP]; Balthazar, José Manoel [UNESP]; Piqueira, José Roberto Castilho (My University, 2011)
The Frequency Modulated - Atomic Force Microscope (FM-AFM) is apowerful tool to perform surface investigation with true atomic resolution. The controlsystem of the FM-AFM must keep constant both the frequency and amplitude ofoscillation of the microcantilever during the scanning process of the sample. However,tip and sample interaction forces cause modulations in the microcantilever motion.A Phase-Locked Loop (PLL) is used as a demodulator and to generate feedback signalto the FM-AFM control system. The PLL performance is vital to the FM-AFMperformace since the image information is in the modulated microcantilever motion.Nevertheless, little attention is drawn to PLL performance in the FM-AFM literature.Here, the FM-AFM control system is simulated, comparing the performancefor di erent PLL designs.
Keywords: Frequency Modulated Atomic Force Microscope; Phase-Locked Loops; Synchronization